Genome Sequence of the Polychlorinated-Biphenyl Degrader Pseudomonas pseudoalcaligenes KF707 - Triscari-Barberi, Tania (American Society for Microbiology, 2012)
Pseudomonas pseudoalcaligenes KF707 is a soil polychlorinated biphenyl (PCB) degrader, able to grow both planktonically and as a biofilm in the presence of various toxic metals and metalloids. Here we report the genome sequence (5,957,359 bp) of P. pseudoalcaligenes KF707, which provides insights into metabolic degradation pathways, flagellar motility, and chemotaxis.